DEVELOPMENT AND EXPERIMENTAL ASSESSMENT OF EFFICIENCY OF THE TECHNICAL SOLUTION FOR DECREASE IN UNORGANIZED DUST EMISSIONS IN THE ATMOSPHERE OF THE CITY - Ekaterina Alekseevna Kaljuzhina; Ivan Aleksandrovich Gvozdkov; Elena Anatolievna Semyonova; Natalia Mihaylovna Sergina (Современная наука и инновации, 2022)
The description and results of trial tests of a technical solution for decrease in unorganized dust emissions in the atmosphere from the electrosteel-smelting furnace are provided in article.